Divine Therapy: Teaching Reflective and Meditative Practices - Carroll, Mary (Teaching theology and religion, 2005)
Reflective and meditative practices, whether Eastern or Western, are being taught in multiple places – retreat houses, hospitals, Zen centers – but are rarely included in the theology classroom. What would be the rationale for inclusion of reflective/meditative practices in a theology curriculum that does not include such a theory/praxis course? What might a mystical tradition/reflective practice course look like? The author first explores the implications of a three-semester pilot program – using guided imagery, spiritual journaling, iconography, and centering prayer – that was conducted with volunteers outside the classroom. Then, based on the experimental project, the author describes a course that blends global traditions with the best of the practices. The author concludes with an evaluation of the reflective/meditative practices and the praxis-inclusive course in terms of possible long-term effects on the personal development of the participants and the ministry of teaching and learning itself.